Penerapan Aplikasi Uji Hipotesis (One-Tail Dan Two-Tail) pada Data Simulasi - Vitri Aprilla Handayani; Luki Hernando (Computer Science and Information Technology, 2022)
Technological developments are now growing rapidly in various layers of science such as in the development of science which has made many changes to the system towards a digital system in solving problems. The use of digital technology in the learning process is considered to increase the learning interest and motivation, the quality of the learning process, and learning outcomes. The younger generation is currently using more of a digital mindset by utilizing increasingly developing technology. Mathematics is one of the basic sciences that always developed to the demands of human needs for technological developments. Mathematics was born because of the human desire to systematize life experiences, organize them, and make them easy to understand, to be able to predict and if possible be able to control events that will occur in the future (forecasting). Problems in mathematics are often considered difficult by the younger generation, for that research will examine the application of desktop-based applications that can solve mathematical problems easily in a shorter time. The application that was built was applied to the One-Tail and Two-Tail hypothesis testing problems on the simulation data.